Testing Newman and Kenworthy's Theory of Density and Automobile Dependence. (June 2018) - Ewing, Reid; Hamidi, Shima; Tian, Guang; Proffitt, David; Tonin, Stefania; Fregolent, Laura
This study tests four hypotheses related to the much-cited work on density and automobile dependence by Newman and Kenworthy, using multivariate analysis and data for 157 large US urbanized areas. We find that density alone explains only a small fraction of the variation in vehicle miles traveled (VMT), and many confounders account for the differences in automobile dependence. We also find that it is not the localized density of individual neighborhoods that causes VMT to be lower in compact urbanized areas but rather the relative accessibility of neighborhoods to the rest of the region.